EFFECT OF TRIBULUS TERRESTRIS ON SERUM LUTEINIZING HORMONE IN SPRAGUE DAWLEY RATS - Hamid, Sidra; Jamil, Aneela; Rashid, Aneeqa; Aziz, Qaiser; Aslam, Muhammad (Pakistan Journal of Physiology, 2017)
Background: Tribulus terrestris is a creeping herb that has been used in the past for treating impotence. The extract obtained from Tribulus mainly contains the active component protodioscin. Administration of the extract improves libido and spermatogenesis. Protodioscin increases the levels of luteinizing hormone (LH), testosterone, dehydroepiandrosterone (DHEA) and dihydrotestosterone (DHT). The objective of present study was to determine the effect of Tribulus terrestris on serum luteinizing hormone in male Sprague Dawley rats. Methods: The study was carried on 60 adult male Sprague Dawley rats aged 90–120 days and with average body weight of 200±50 grams. Rats were divided into two groups with 30 rats per group. Group A received 0.5 ml distilled water once daily orally. Group B was administered orally Tribulus aqueous extract 6 mg/Kg once daily. All the doses were given to rats for 8 weeks. After 8 weeks, serum luteinizing hormone was measured in both groups. The mean values of LH were compared using SPSS. Alpha value was kept at 0.05. Results: The mean LH level was 1.26±0.54 for control group while it was 1.75±0.65 for the experimental group. The difference between control group and experimental group was statistically significant (p<0.001). Conclusion: Tribulus terrestris increases the levels of LH when administered in appropriate doses. Pak J Physiol 2017;13(4):38–40